Predictive factors of extubation failure in pediatric cardiac intensive care unit: A single-center retrospective study from Thailand - Saengsin, Kwannapas; Sittiwangkul, Rekwan; Borisuthipandit, Thirasak; Trongtrakul, Konlawij; Tanasombatkul, Krittai; Phanacharoensawad, Thanaporn; Moonsawat, Guanoon; Phinyo, Phichayut (Frontiers in Pediatrics, 2023)
Introduction/objective Extubation failure increases morbidity and mortality in pediatric cardiac patients, a unique population including those with congenital heart disease or acquired heart disease. This study aimed to evaluate the predictive factors of extubation failure in pediatric cardiac patients and to determine the association between extubation failure and clinical outcomes. Methods We conducted a retrospective study in the pediatric cardiac intensive care unit (PCICU) of the Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand, from July 2016 to June 2021. Extubation failure was defined as the re-insertion of the endotracheal tube within 48 hours after extubation. Multivariable log-binomial regression with generalized estimating equations (GEE) was performed to explore the predictive factors associated with extubation failure. Results We collected 318 extubation events from 246 patients. Of these, 35 (11%) events were extubation failures. In physiologic cyanosis, the extubation failure group had significantly higher SpO2 than the extubation success group (P < 0.001). The predictive factors associated with extubation failure included a history of pneumonia before extubation (RR 3.09, 95% CI 1.54–6.23, P = 0.002), stridor after extubation (RR 2.57, 95% CI 1.44–4.56, P = 0.001), history of re-intubation (RR 2.24, 95% CI 1.21–4.12, P = 0.009), and palliative surgery (RR 1.87, 95% CI 1.02–3.43, P = 0.043). Conclusion Extubation failure was identified in 11% of extubation attempts in pediatric cardiac patients. The extubation failure was associated with a longer duration of PCICU stay but not with mortality. Patients with a history of pneumonia before extubation, history of re-intubation, post-operative palliative surgery, and post-extubation stridor should receive careful consideration before extubation and close monitoring afterward. Additionally, patients with physiologic cyanosis may require balanced circulation via regulated SpO2.